スイショウ オンドケイ ヲ モチイタ ショウワキチ デノ チチュウ オヨビ カイスイ オンド ノ セイミツ レンゾク ソクテイ - 渋谷, 和雄; シブヤ, カズオ; 長尾, 年恭; ナガオ, トシヤス; 神沼, 克伊; カミヌマ, カツタダ; Shibuya, Kazuo; Nagao, Toshiyasu; Kaminuma, Katsutada (1982)
P(論文) 8カ月間の地中温度連続観測が, 昭和基地の20m岩盤ボーリング孔を用いて行われた。特別に設計された水晶温度計による観測の結果, 深さ5mでは-4.89℃から-10.36℃(変動幅5.47℃)の間で正弦関数的な変動を示すことがわかった。上記の変動幅は10mの深さでは1.58℃(-7.73℃∿-9.31℃)となり, 20mの深さでは0.20℃(-8.17℃∿-8.37℃)となる。気温の季節変動にくらべ地中温度の極大, 極小の表れる時期には位相の遅れが生じるが, その値は深さ5mで約90日, 深さ20mでは約290日に達することがわかった。また, 気象変動が地中温度に及ぼす影響に, 指数関数的な減衰をあてはめると33.8mの深さで0.01℃の変動幅におさまるはずである。海水温の連続測定も6カ月間にわたり, オングル島西の浦の海氷下7mの海水中で行われた。それによると6月上旬の-1.63℃から11月下旬の-1.48℃まで大体0.9×10^<-3>℃/日の割合で海水温は上昇した。さらに上記の傾向にかぶさるように10-30日の短かい周期を持つ0.05-0.10℃の変動が認められ, それは突然温度が上昇し, その後ゆるやかに下降していくパターンの繰り返しで特徴づけられる。 Eight-months' observation of underground temperature was made by specially designed quartz thermometers in a 20m borehole at Syowa Station, East Antarctica. The underground temperature at 5m depth showed a quasisinusoidal change of 5.47℃ from -4.89℃ to -10.36℃. The above change became smaller to 1.58℃ in the range of -7.73℃∿-9.31℃ at 10m depth, and became further smaller to 0.20℃ in the range of -8.17℃∿-8.37℃ at 20m depth. In comparison with the seasonal variation of air temperature, there was a phase delay of about 90 days at 5m depth and about 290 days at 20m depth. The effect of the seasonal variation of air temperature on that of underground temperature can be estimated as less than 0.01℃ at the depth of 33.8m when exponential decay against depth is assumed to have resulted from such effect. Six-months' observation of sea-water temperature was also made at 7m depth under the ice-cover of the coast of Nisi-no-ura Cove. The observation revealed a gradual increase of temperature from -1.63℃ in June to -1.48℃ in November at an approximate rate of 0.9×10^<-3>℃/day. Superposed on the above longterm trend, there was a sequence of short-term (10-30 days) variations of 0.05-0.10℃ which was characterized by the abrupt increase and the subsequent gradual decrease of temperature. departmental bulletin paper